Implementation of Legal Certainty Regarding the Terms of the Fixed Term Employment Agreement in Job Creation Law - Bening Cahyaningtyas; Adhining Prabawati Rahmahani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Job Creation Law, particularly regarding the employment law cluster, does not optimally implement legal certainty, resulting in weakened legal protection for workers. The problem formulation in this study is how legal protection for workers with contract status, and how legal certainty is implemented in the provisions of the fixed-term employment agreement (PKWT). This study applies normative juridical methods and a statutory approach, examines regulations based on legislation, and is supported by relevant primary, secondary, and tertiary legal sources. The results show that legal uncertainty in the provisions of the PKWT period creates legal loopholes and creates opportunities for flexibility, which has the potential to weaken workers' basic rights. Legal certainty in the provisions of the PKWT period plays a crucial role because it is directly related to legal protection for workers' basic rights. Regulations containing legal certainty aim to ensure that provisions are clear, predictable, fair, and do not create legal loopholes that could harm either party. The study concludes that the implementation of legal certainty in the provisions of PKWT is not optimal, which does not provide certainty for workers so that workers become continuous contract workers, resulting in weakened legal protection for workers. Therefore, the government needs to improve regulations and increase supervision, in order to create ideal and fair industrial relations.